2019
DOI: 10.1002/art.40869
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden in Osteoarthritis Is Similar to That of Rheumatoid Arthritis at Initial Rheumatology Visit and Significantly Greater Six Months Later

Abstract: Objective To analyze disease burden in osteoarthritis (OA) according to Multidimensional Health Assessment Questionnaire (MDHAQ)/Routine Assessment of Patient Index Data 3 (RAPID3) scores at the initial visit and the 6‐month follow‐up visit, compared with rheumatoid arthritis (RA) as a benchmark for high disease burden. Methods All patients with all diagnoses at the Rush University Medical Center Division of Rheumatology complete a paper MDHAQ at all visits, saved as a PDF in the electronic health record. MDHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Given its prevalence in the community, even relatively small excesses in work disability are likely to contribute significantly to the overall burden. Combining this with the suggestion from a recent US study that disability from OA may be more recalcitrant to medical intervention compared to inflammatory disease, then we have another significant musculoskeletal contributor to the overall burden of work disability.…”
supporting
confidence: 53%
“…Given its prevalence in the community, even relatively small excesses in work disability are likely to contribute significantly to the overall burden. Combining this with the suggestion from a recent US study that disability from OA may be more recalcitrant to medical intervention compared to inflammatory disease, then we have another significant musculoskeletal contributor to the overall burden of work disability.…”
supporting
confidence: 53%
“…The observation of higher depression screening scores on MDHAQ, PHQ-9, and HADS-D, as well as higher scores on almost all other MDHAQ items in patients with SpA versus RA, is not widely recognized (43,44). Rheumatic diseases differ widely in pathophysiology and treatment from the perspective of health professionals but are associated with common similar problems from the perspective of patients, including functional disability, pain, fatigue, and comorbidities, including depression (19,42).…”
Section: Discussionmentioning
confidence: 99%
“…In our work the changes in soft-tissue phase MCCR between baseline and 1-month follow-up post-therapy seems to be generally higher compared to the delayed osseous phase MCCR. The finding of increased soft-tissue phase MCCR in Group II (osteoarthritis) joints in individual participants categorized as responders to RA therapy may be supported by recently published work (34) demonstrating that, in independent patient groups with RA and OA, both diseases showed similar disease burden at presentation to rheumatologists; however, after treatment, OA was associated with a higher mean burden of disease than RA. A recent meta-analysis showed that RA-targeted therapies may not offer clinically significant pain relief above placebo in symptomatic OA (35).…”
Section: Discussionmentioning
confidence: 57%